Meningkatkan Literasi Digital Bagi Calon Profesional Kesehatan di SMK Kesdam IV/Diponegoro Magelang - Tika Sari Dewi; Suryo Nugroho Markus; Ratna Prahesti (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Backgroud: digital literacy competencies. Health professional education that prepares prospective health professionals is obliged to prepare prospective graduates to be able to improve their skills and be responsible in using health information technology. Health professional education has not been able to provide support for creating digital literacy in the education environment. Service objectives: Increase digital literacy competency with material that focuses on search strategies with journal information, maintaining confidentiality of patient data and ethics in using information technology. Method: This service was carried out offline at SMK Kesdam IV/Diponegoro Magelang involving 45 students consisting of 2 majors, namely nursing assistant and medical laboratory technology. The analysis used to assess the impact of training is quantitative descriptive by displaying frequency and percentage data. Providing digital literacy training to students at SMK Kesdam IV/Diponegoro as prospective health workers. Results: The digital literacy training given to students was able to significantly increase students' skills and knowledge related to digital literacy.